OPTIMALISASI BELANJA MASYARAKAT MELALUI MEDIA SOSIAL TIKTOK SHOP - Luqiana, Zalfa Azahra; Revina, Revina; Wahyudi , Shifa Ashila; Putry , Andieni (Universitas Haji Sumatera Utara, 2024)
The development of information and communication technology (ICT) has significantly transformed consumer behavior patterns, especially in shopping activities. TikTok Shop has become a leading online shopping platform in Indonesia, leveraging advances in the internet and social media. However, research on the factors influencing consumer trust and loyalty on TikTok Shop remains limited. This study aims to develop a model of consumer trust and loyalty specifically for TikTok Shop in Indonesia by identifying factors such as transaction security, product quality, interaction with sellers, and user experience. This research uses a descriptive qualitative approach, with data collected through a Google Form questionnaire from 56 TikTok users. The results show that most respondents are satisfied with their shopping experience on TikTok Shop, primarily due to discounts, affordable prices, and live streaming features. However, there are some shortcomings, such as slow delivery and a lack of free shipping offers. This study provides practical insights for sellers and platform developers to enhance consumer satisfaction and loyalty by improving TikTok Shop's features and services.